2002
DOI: 10.1103/physrevlett.88.124801
|View full text |Cite
|
Sign up to set email alerts
|

Single-Shot Electron-Beam Bunch Length Measurements

Abstract: We report subpicosecond electro-optic measurements of the length of individual relativistic electron bunches. The longitudinal electron-bunch shape is encoded electro-optically on to the spectrum of a chirped laser pulse. The electron-bunch length is determined by analyzing individual laser-pulse spectra obtained with and without the presence of an electron bunch. Since the length of the chirped laser pulse can be easily changed, the electron bunch can be visualized on different time scales. This single-shot i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(117 citation statements)
references
References 19 publications
2
114
0
Order By: Relevance
“…$100 fs the temporal profile is faithfully reproduced by integrating the resulting signal over frequency. This is consistent with other techniques [2,3,8]. As the bunch length becomes shorter, the frequency components that define its shape exist on both the low and high frequency sides of the transverse phonon resonance.…”
Section: Numerical Results and Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…$100 fs the temporal profile is faithfully reproduced by integrating the resulting signal over frequency. This is consistent with other techniques [2,3,8]. As the bunch length becomes shorter, the frequency components that define its shape exist on both the low and high frequency sides of the transverse phonon resonance.…”
Section: Numerical Results and Discussionsupporting
confidence: 75%
“…The next advancement in EOS was the development of a single shot technique that relies on spectral decoding [3,7,8,16]. Here instead of an ultrashort pulse, a stretched pulse is used as a probe and only the polarization state corresponding to the 1 " 10 axis is examined.…”
Section: A Current Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…If a crystal is placed adjacent to the electron beam, its index of refraction will be distorted anisotropically by the strong electromagnetic fields associated with the ultrarelativistic electrons [9,10]. This transient birefringence or electro-optic effect is induced without affecting the electron bunch propagation.…”
mentioning
confidence: 99%
“…While the Coulomb field is always present, coherent radiation is emitted only in special geometries, for example when the electron bunches propagate through a bending magnet, a thin metal foil (transition radiation), or a slit or a hole in a metal (diffraction radiation). It was shown that the Coulomb field of sub-ps electron bunch structures with some 100 pC charge can be measured with about 200 fs resolution by the spectral decoding technique [3,4]. Also, measuring the coherent transition radiation has proven to be a suitable method to analyze the temporal profiles of electron bunches [5].…”
Section: Introductionmentioning
confidence: 99%